Empowering farmers with improved finger millet production technologies for higher productivity - Chapke, Rajendra R.; Srinivas, A.; Anuradha, N.; Swarna, R.; Sreeleela, Y.; Laxmiprasanna, P. (Indian Farming, 2025)
Finger millet is a highly nutritious and climate-resilient crop, primarily cultivated for both food and fodder. It thrives in sub-tropical climates at high altitudes and is notable for its high calcium, dietary fiber and high quality protein, making it a highly nutritious grain. India produces 1.8 million tonnes annually, with Karnataka contributing about 60%. The crop adapts well to kharif season rainfed conditions and prefers loamy to sandy soils with good drainage. Various improved and nutrient-rich varieties were developed with resistance to major diseases and pests. Improved practices such as proper land preparation, seed treatment, spacing, timely irrigation and weed control enhance productivity. Intercropping with legumes and crop rotation with pulses improve soil fertility and yield sustainability, making finger millet an ideal crop for climate-resilient and nutrition-sensitive agriculture. Improved finger millet production interventions led to notable increases in yield and profitability, achieving up to a 21% gain compared to existing traditionaltechniques.